2019
DOI: 10.1155/2019/9159267
|View full text |Cite
|
Sign up to set email alerts
|

Research Methods and Progress of Patellofemoral Joint Kinematics: A Review

Abstract: Patellofemoral pain syndrome has a high morbidity, and its pathology is closely associated with patellofemoral joint kinematics. A series of in vivo and in vitro studies have been conducted to explore patellofemoral kinematics, and the findings are relevant to the diagnosis, classification, and management of patellofemoral diseases and even the whole knee joint. However, no definite conclusion on normal patellofemoral kinematics has been established. In this study, the measurement methodologies of patellofemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…This systematic review expands our clinical and research understanding regarding the origin of PFP, by providing quantitative evidence of the specific confounding variables’ influence, or lack thereof, on our ability to distinguish patellofemoral kinematics measured in patients with PFP from the kinematics measured in asymptomatic controls. This sets it apart from past reviews that attempted to generate a normative patellofemoral kinematic profile across studies 30,79 or sought to define which factors are most associated with patellofemoral pain (eg, sulcus angle, tibiofemoral alignment, bisect offset). 13,34 Irrespective of interstudy differences, this review presents strong evidence that lateral patellar shift and tilt maltracking are significantly associated with PFP_iso and PFP_dis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review expands our clinical and research understanding regarding the origin of PFP, by providing quantitative evidence of the specific confounding variables’ influence, or lack thereof, on our ability to distinguish patellofemoral kinematics measured in patients with PFP from the kinematics measured in asymptomatic controls. This sets it apart from past reviews that attempted to generate a normative patellofemoral kinematic profile across studies 30,79 or sought to define which factors are most associated with patellofemoral pain (eg, sulcus angle, tibiofemoral alignment, bisect offset). 13,34 Irrespective of interstudy differences, this review presents strong evidence that lateral patellar shift and tilt maltracking are significantly associated with PFP_iso and PFP_dis.…”
Section: Discussionmentioning
confidence: 99%
“…Data from all studies in the final database were extracted and tabulated. The potential sources of intra- and interstudy variability 30,79 were identified during data extraction. These sources fell into 3 main categories: demographics, study design, and outcome measurement techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patellar maltracking is a common concern in the management of patellofemoral disorders [3,4]. However, high dependence on the coordinate system of patellar tracking leads to ambiguity in the consensus of the definition of normal tracking [5,6], and therefore is not accurate enough when evaluating patellofemoral kinematics with patellar tracking.…”
Section: Introductionmentioning
confidence: 99%
“…If focus merely on patellar tracking, there could be some inevitable disadvantages. High dependence on the coordinate system of patellar tracking has made the comparison among research results difficult, which led to the ambiguity to consensus of normal patellar tracking [4,5]. To deal with patellofemoral disorders, it is crucial to fully understand the in vivo patellofemoral kinematics.…”
Section: Introductionmentioning
confidence: 99%